High-frequency low-power-consumption Fe-Si-Al soft magnetic material as well as preparation method and application thereof

By using an insulating coating solution prepared by aluminum phytate sol and silicon sol, the ferrosilicon aluminum soft magnetic alloy powder is insulated and a silica-aluminum phosphate composite coating is generated through high-temperature heat treatment, which solves the problem of large eddy current loss in high-frequency applications of existing ferrosilicon aluminum soft magnetic materials, and achieves efficient insulating coating and simplified processes.

CN119763969AActive Publication Date: 2025-04-04广东泛瑞新材料股份有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411972154.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing ferrosilicon aluminum soft magnetic materials have large eddy current losses in high-frequency applications, resulting in energy loss and heating problems. The process of double-layer insulation coating is complex and has poor stability.

Method used

The insulating coating solution was prepared by mixing aluminum phytate sol and silica sol, and insulating coating was carried out on the ferrosilicon aluminum soft magnetic alloy powder, and a silica-aluminum phosphate composite coating was formed by high-temperature heat treatment, which simplified the insulating coating treatment.

Benefits of technology

It significantly improves the insulation coating effect, reduces high-frequency power consumption, simplifies production processes and reduces costs, while improving the high-frequency and magnetic properties of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of soft magnetic materials, and discloses a high-frequency low-power-consumption Fe-Si-Al soft magnetic material and a preparation method and application thereof. The preparation method comprises the following steps: adding phytic acid into an alcohol-water solution for dissolving, then adding an aluminum alkoxide solution for mixing reaction to obtain phytic acid aluminum sol, and then uniformly mixing the phytic acid aluminum sol with silica sol to obtain an insulating coating solution; carrying out coating treatment on Fe-Si-Al magnetically soft alloy powder by adopting the insulating coating liquid, then heating to 300-800 DEG C, and carrying out heat treatment, so as to obtain alloy powder subjected to insulating coating treatment by adopting a silicon dioxide-aluminum phosphate compound; and finally, mixing the Fe-Si-Al soft magnetic material with a binder, performing compression molding, heating to 600-900 DEG C, and performing annealing treatment to obtain the high-frequency low-power-consumption Fe-Si-Al soft magnetic material. The soft magnetic alloy powder is subjected to insulation coating by adopting the insulation coating liquid prepared by mixing the phytic acid aluminum sol and the silica sol, so that the insulation coating effect can be remarkably improved, and the high-frequency loss of a magnetic ring product is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of soft magnetic materials, and in particular relates to a high-frequency, low-power consumption sendust soft magnetic material and a preparation method and application thereof. Background Art

[0002] Iron silicon aluminum (FeSiAl) soft magnetic alloy refers to a high magnetic permeability soft magnetic alloy with iron silicon aluminum as the main component, also known as sendust alloy. The alloy has the remarkable characteristics of magnetic anisotropy coefficient and saturation hysteresis coefficient approaching zero. Compared with other soft magnetic alloy materials, FeSiA1 soft magnetic alloy material has the comprehensive advantages of low loss, high resistance, low cost and no noise, making it popular.

[0003] Sendust cores are mainly used in high-frequency fields. As the operating frequency increases, the rate of eddy current loss increases very quickly. Eddy current loss not only reduces the performance of the magnetic core, but also causes the device to heat up. With the improvement of electronic technology, the requirements for magnetic devices are getting higher and higher, mainly developing in the direction of miniaturization and high frequency, and higher requirements are put forward for magnetic loss and temperature rise performance. In order to reduce the energy loss caused by eddy current loss, it is key to reduce the conductivity of the magnetic core and increase its resistivity. A common treatment method is to perform insulating coating treatment on the surface of the magnetic core particles. For example, in the patent document with publication number CN1965379A, a soft magnetic material containing composite magnetic particles is disclosed, and the composite magnetic particles are composed of metal magnetic particles mainly composed of Fe and an insulating coating layer covering the metal magnetic particles. The insulating coating layer contains iron phosphate compounds and aluminum phosphate compounds. The atomic ratio of Fe contained in the contact surface of the insulating coating layer in contact with the metal magnetic particles is greater than the atomic ratio of Fe contained in the surface of the insulating coating layer. The atomic ratio of A contained in the surface of the insulating coating layer in contact with the metal magnetic particles is less than the atomic ratio of Al contained in the surface of the insulating coating layer. With this structure, iron loss can be reduced. Its main technology is that the contact surface of the insulating coating layer in contact with the metal magnetic particles is formed by a layer containing a large amount of phosphoric acid and Fe. The layer containing a large amount of phosphoric acid and Fe has high adhesion to Fe, thereby improving the adhesion between the metal magnetic particles and the insulating coating layer. Therefore, the insulating coating layer is hardly broken during pressure molding and the increase of eddy current loss can be suppressed. In addition, the surface of the insulating coating layer is formed by a layer containing a large amount of phosphoric acid and at least one atom selected from Al, Si, Mn, Ti, Zr and Zn. Compared with the layer containing a large amount of phosphoric acid and Fe, the layer containing a large amount of phosphoric acid and at least one atom selected from Al, Si, Mn, Ti, Zr and Zn has excellent high temperature stability, so that when it is heated at high temperature, the soft magnetic material does not break. In addition, this layer also suppresses the decomposition of the layer formed on the contact surface of the insulating coating layer in contact with the metal magnetic particles. Therefore, the heat resistance of the insulating coating layer can be improved, and the hysteresis loss of the powder magnetic core prepared by press-molding such a soft magnetic material can be reduced without reducing the eddy current loss. Therefore, the iron loss of the powder magnetic core can be reduced.

[0004] However, the prior art requires a double-layer insulation coating to improve the insulation coating effect, and the preparation process is complex and the stability is poor. Summary of the invention

[0005] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing a high-frequency and low-power consumption Sendust soft magnetic material.

[0006] Another object of the present invention is to provide a high-frequency, low-power consumption Sendust soft magnetic material prepared by the above method.

[0007] Another object of the present invention is to provide the application of the above-mentioned high-frequency, low-power consumption iron silicon aluminum soft magnetic material in the fields of AI computing chips, servers and communication equipment.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material, comprising the following preparation steps:

[0010] (1) Preparation of insulating coating liquid: adding phytic acid to an alcohol aqueous solution to dissolve, then adding an aluminum alkoxide solution to mix and react to obtain a phytic acid aluminum sol, which is then mixed evenly with a silica sol to obtain an insulating coating liquid;

[0011] (2) Insulation coating treatment: uniformly mixing the sendust soft magnetic alloy powder with the insulation coating liquid of step (1), first drying at a temperature of 60 to 100° C. to remove the solvent, and then heating to 300 to 800° C. for heat treatment to obtain an alloy powder with insulation coating treatment of a silicon dioxide-aluminum phosphate composite;

[0012] (3) Pressing and molding: The alloy powder treated with the insulation coating of the silicon dioxide-aluminum phosphate composite is mixed evenly with the binder, and then injected into a mold for pressing and molding, and then heated to 600-900°C for annealing to obtain a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material.

[0013] Preferably, the alcohol aqueous solution in step (1) is an ethanol aqueous solution having an ethanol volume percentage of 80 to 95%.

[0014] Preferably, the aluminum alkoxide solution in step (1) is aluminum triethoxide solution, aluminum propoxide solution, aluminum isopropoxide solution or aluminum n-butoxide solution.

[0015] Preferably, the amount of aluminum alkoxide solution added in step (1) makes the pH value of the reaction system be 5 to 7.

[0016] Preferably, the amount of silica sol added in step (1) is 20 to 60% of the mass of phytic acid in terms of silicon dioxide content.

[0017] Preferably, the D50 particle size of the Sendust soft magnetic alloy powder in step (2) is 5 to 15 um.

[0018] Preferably, the amount of the insulating coating liquid added in step (2) is 0.2-2% of the mass of the Sendust soft magnetic alloy powder in terms of solid content.

[0019] Preferably, the drying and removing of the solvent in step (2) is carried out under vacuum conditions; the heat treatment is carried out under nitrogen protection conditions, and the heat treatment time is 3 to 10 hours.

[0020] Preferably, the adhesive in step (3) is an epoxy resin adhesive solution or a silicone resin adhesive solution.

[0021] Preferably, the amount of the binder added in step (3) is 0.2 to 1% of the mass of the alloy powder subjected to the insulation coating treatment, calculated as its solid content.

[0022] Preferably, the temperature of the compression molding in step (3) is 60-100° C. and the pressure is 500-800 MPa.

[0023] Preferably, the annealing treatment time in step (3) is 15 to 120 minutes.

[0024] A high-frequency, low-power-consumption sendust soft magnetic material is prepared by the above method.

[0025] The above-mentioned high-frequency, low-power iron-silicon-aluminum soft magnetic materials are used in the fields of AI computing chips, servers and communication equipment.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention uses an insulating coating liquid prepared by mixing phytic acid aluminum sol and silica sol to perform insulating coating on the iron-silicon-aluminum soft magnetic alloy powder, wherein the phytic acid molecules have good adhesion to the surface of the soft magnetic alloy powder, thereby significantly improving the coating effect. Through subsequent high-temperature heat treatment, a high-temperature and high-pressure resistant silicon dioxide-aluminum phosphate composite coating layer can be generated in situ on the surface of the soft magnetic alloy powder, wherein aluminum phosphate serves as a support carrier that is resistant to high temperatures, improves bonding strength and reduces brittleness, and silicon dioxide serves as a coating component that improves insulation performance. Through the composite coating of the two, the insulating coating effect can be significantly improved, thereby improving the high-frequency power consumption performance of the product.

[0028] (2) The insulating coating layer of the silica-aluminum phosphate composite of the present invention can further improve the bonding strength with the binder resin, thereby improving the molding density and magnetic properties of the magnetic core.

[0029] (3) The present invention adopts a one-step insulation coating process, which can simplify the production process and reduce production costs. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0031] Example 1

[0032] A method for preparing a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material, comprising the following preparation steps:

[0033] (1) Preparation of insulation coating liquid: phytic acid is added to an ethanol aqueous solution with an ethanol volume percentage of 85% to dissolve, and then an ethanol solution of aluminum isopropoxide is added for mixed reaction, and the pH value of the reaction system is controlled to be 6 by controlling the amount of aluminum isopropoxide added to obtain phytic acid aluminum sol. Then, the phytic acid aluminum sol is evenly mixed with silica sol, and the amount of silica sol added is 40% of the mass of phytic acid in terms of silicon dioxide content, to obtain an insulation coating liquid with a solid content of 20%.

[0034] (2) Insulation coating treatment: The sendust soft magnetic alloy powder with a D50 particle size of 10 um and the insulation coating liquid of step (1) are mixed evenly by high-speed stirring. The amount of insulation coating liquid added is 0.5% of the mass of the sendust soft magnetic alloy powder in terms of its solid content. The powder is first dried in vacuum at 80°C to remove the solvent, and then heated to 500°C under nitrogen protection for heat treatment for 5 hours to obtain an alloy powder with insulation coating of a silicon dioxide-aluminum phosphate composite.

[0035] (3) Pressing: The alloy powder treated with the insulation coating of the silicon dioxide-aluminum phosphate composite was mixed evenly with the epoxy resin ethanol solution binder (solid content 15%), wherein the epoxy resin content was 0.4% of the mass of the alloy powder treated with the insulation coating. The mixture was then injected into a ring-shaped mold and pressed at a pressure of 600 MPa and a temperature of 80°C. The mixture was then heated to 750°C under nitrogen protection and annealed for 60 minutes to obtain a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material (magnetic ring).

[0036] The outer diameter of the magnetic ring obtained in this embodiment is 10 mm, the inner diameter is 6 mm, the height is 3.4 mm, and the density is 5.892 g / cm 3 , the inductance value L is 16.60μH, and the high-frequency loss (1MHz / 50mT) is 1091kW / m 3 .

[0037] Example 2

[0038] A method for preparing a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material, comprising the following preparation steps:

[0039] (1) Preparation of insulation coating liquid: phytic acid is added to an ethanol aqueous solution with an ethanol volume percentage of 90% to dissolve, and then an ethanol solution of aluminum triethoxide is added for mixed reaction, and the pH value of the reaction system is controlled to be 5 by controlling the amount of aluminum triethoxide added to obtain phytic acid aluminum sol. Then, the phytic acid aluminum sol is evenly mixed with silica sol, and the amount of silica sol added is 20% of the mass of phytic acid in terms of silicon dioxide content, to obtain an insulation coating liquid with a solid content of 20%.

[0040] (2) Insulation coating treatment: The sendust soft magnetic alloy powder with a D50 particle size of 5 um and the insulation coating liquid of step (1) are mixed uniformly by high-speed stirring. The amount of insulation coating liquid added is 1.5% of the mass of the sendust soft magnetic alloy powder in terms of its solid content. The powder is first dried in vacuum at 80°C to remove the solvent, and then heated to 600°C under nitrogen protection for heat treatment for 6 hours to obtain an alloy powder with insulation coating of a silicon dioxide-aluminum phosphate composite.

[0041] (3) Pressing: The alloy powder treated with the insulation coating of the silicon dioxide-aluminum phosphate composite was mixed evenly with the epoxy resin ethanol solution binder (solid content 15%), wherein the epoxy resin content was 0.6% of the mass of the alloy powder treated with the insulation coating. The mixture was then injected into a ring-shaped mold and pressed at a pressure of 700 MPa and a temperature of 80°C. The mixture was then heated to 750°C under nitrogen protection and annealed for 60 minutes to obtain a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material (magnetic ring).

[0042] The outer diameter of the magnetic ring obtained in this embodiment is 10 mm, the inner diameter is 6 mm, the height is 3.4 mm, and the density is 5.827 g / cm 3 , the inductance value L is 15.33μH, and the high-frequency loss (1MHz / 50mT) is 1150kW / m 3 .

[0043] Example 3

[0044] A method for preparing a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material, comprising the following preparation steps:

[0045] (1) Preparation of insulation coating liquid: phytic acid is added to an ethanol aqueous solution with an ethanol volume percentage of 95% to dissolve, and then an ethanol solution of aluminum isopropoxide is added for mixed reaction, and the pH value of the reaction system is controlled to be 7 by controlling the amount of aluminum isopropoxide added to obtain phytic acid aluminum sol. Then, the phytic acid aluminum sol is evenly mixed with silica sol, and the amount of silica sol added is 60% of the mass of phytic acid in terms of silicon dioxide content, to obtain an insulation coating liquid with a solid content of 20%.

[0046] (2) Insulation coating treatment: The sendust soft magnetic alloy powder with a D50 particle size of 15 um and the insulation coating liquid of step (1) are mixed evenly by high-speed stirring. The amount of insulation coating liquid added is 1% of the mass of the sendust soft magnetic alloy powder in terms of its solid content. The powder is first dried in vacuum at 80°C to remove the solvent, and then heated to 700°C under nitrogen protection for heat treatment for 4 hours to obtain an alloy powder with insulation coating of a silicon dioxide-aluminum phosphate composite.

[0047] (3) Compression molding: The alloy powder treated with the insulation coating of the silica-aluminum phosphate composite is mixed evenly with an ethanol solution binder of a silicone resin (a low-viscosity vinyl silicone oil and hydrogen-containing silicone oil bonding and curing system) (solid content 10%), wherein the content of the silicone resin is 0.2% of the mass of the alloy powder treated with the insulation coating. The mixture is then injected into a ring-shaped mold and pressed at a pressure of 800 MPa and a temperature of 80°C. The mixture is then heated to 750°C under nitrogen protection and annealed for 60 minutes to obtain a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material (magnetic ring).

[0048] The outer diameter of the magnetic ring obtained in this embodiment is 10 mm, the inner diameter is 6 mm, the height is 3.4 mm, and the density is 5.916 g / cm 3 , the inductance value L is 16.70μH, and the high-frequency loss (1MHz / 50mT) is 1090kW / m 3 .

[0049] Comparative Example 1

[0050] A method for preparing a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material, comprising the following preparation steps:

[0051] (1) Preparation of insulating coating liquid: phytic acid is added to an ethanol aqueous solution with an ethanol volume percentage of 85% to dissolve, and then an ethanol solution of aluminum isopropoxide is added to mix and react. The pH value of the reaction system is adjusted to 6 by controlling the amount of aluminum isopropoxide added to obtain a phytic acid aluminum sol insulating coating liquid with a solid content of 20%.

[0052] The preparation process of (2) to (3) is the same as that of Example 1.

[0053] The magnetic ring obtained in this comparative example has an outer diameter of 10 mm, an inner diameter of 6 mm, a height of 3.4 mm, and a density of 5.902 g / cm 3 , the inductance value L is 16.87μH, and the high-frequency loss (1MHz / 50mT) is 1925kW / m 3 .

[0054] By comparing the results with those of Example 1, it can be concluded that the inductance of the magnetic ring obtained by simply using aluminum phosphate insulation coating treatment increases slightly, but the high-frequency loss also increases significantly, indicating that the composite silicon dioxide coating layer is beneficial to improving the insulation performance.

[0055] Comparative Example 2

[0056] A method for preparing a high-frequency, low-power consumption iron-silicon-aluminum soft magnetic material. Compared with Example 1, a silica sol with a solid content of 20% is used as an insulating coating liquid, and the rest of the preparation process is the same as that of Example 1.

[0057] The magnetic ring obtained in this comparative example has an outer diameter of 10 mm, an inner diameter of 6 mm, a height of 3.4 mm, and a density of 5.680 g / cm 3 , the inductance value L is 12.93μH, and the high-frequency loss (1MHz / 50mT) is 2261kW / m 3 .

[0058] By comparing the results with those of Example 1, it can be concluded that the density and inductance of the magnetic ring obtained by simply using silicon dioxide insulation coating treatment are significantly reduced, and the high-frequency loss is significantly increased. This shows that the composite aluminum phosphate coating layer of the present invention is conducive to improving the coating effect and can also improve the bonding performance.

[0059] Comparative Example 3

[0060] A method for preparing a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material, comprising the following preparation steps:

[0061] (1) Preparation of insulation coating liquid: phosphoric acid is added to an ethanol aqueous solution with an ethanol volume percentage of 85% to dissolve, and then an ethanol solution of aluminum isopropoxide is added to mix and react, and the pH value of the reaction system is controlled to be 6 by controlling the amount of aluminum isopropoxide added to obtain an aluminum phosphate dispersion. Then, it is evenly mixed with silica sol, and the amount of silica sol added is 40% of the mass of phosphoric acid based on the silicon dioxide content, to obtain an insulation coating liquid with a solid content of 20%.

[0062] The preparation process of (2) to (3) is the same as that of Example 1.

[0063] The magnetic ring obtained in this comparative example has an outer diameter of 10 mm, an inner diameter of 6 mm, a height of 3.4 mm, and a density of 5.736 g / cm 3 , the inductance value L is 13.14μH, and the high-frequency loss (1MHz / 50mT) is 2837kW / m 3 .

[0064] By comparing the results with those of Example 1, it can be concluded that the insulation coating liquid prepared by mixing the aluminum phosphate dispersion obtained by the reaction of phosphoric acid and aluminum alkoxide solution with silica sol has a significantly reduced insulation coating effect, resulting in a significant increase in high-frequency loss.

[0065] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a high-frequency, low-power-consumption sendust soft magnetic material, characterized in that: The method comprises the following preparation steps: (1) Preparation of insulating coating liquid: adding phytic acid to an alcohol aqueous solution to dissolve, then adding an aluminum alkoxide solution to mix and react to obtain a phytic acid aluminum sol, which is then mixed evenly with a silica sol to obtain an insulating coating liquid; (2) Insulation coating treatment: uniformly mixing the sendust soft magnetic alloy powder with the insulation coating liquid of step (1), first drying at a temperature of 60 to 100° C. to remove the solvent, and then heating to 300 to 800° C. for heat treatment to obtain an alloy powder with insulation coating treatment of a silicon dioxide-aluminum phosphate composite; (3) Pressing and molding: The alloy powder treated with the insulation coating of the silicon dioxide-aluminum phosphate composite is mixed evenly with the binder, and then injected into a mold for pressing and molding, and then heated to 600-900°C for annealing to obtain a high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material.

2. The method for preparing a high-frequency, low-power-consumption Sendust soft magnetic material according to claim 1, characterized in that: The alcohol aqueous solution in step (1) is an ethanol aqueous solution with an ethanol volume percentage of 80-95%; the aluminum alkoxide solution is an aluminum triethanolate solution, an aluminum propoxide solution, an aluminum isopropoxide solution or an aluminum n-butoxide solution.

3. The method for preparing a high-frequency, low-power-consumption Sendust soft magnetic material according to claim 1, characterized in that: The amount of aluminum alkoxide solution added in step (1) is such that the pH value of the reaction system is 5 to 7; the amount of silica sol added is 20 to 60% of the mass of phytic acid in terms of silicon dioxide content.

4. The method for preparing a high-frequency, low-power-consumption Sendust soft magnetic material according to claim 1, characterized in that: The D50 particle size of the Sendust soft magnetic alloy powder in step (2) is 5 to 15 um.

5. The method for preparing a high-frequency, low-power-consumption Sendust soft magnetic material according to claim 1, characterized in that: The amount of the insulating coating liquid added in step (2) is 0.2-2% of the mass of the Sendust soft magnetic alloy powder in terms of solid content.

6. The method for preparing a high-frequency, low-power-consumption Sendust soft magnetic material according to claim 1, characterized in that: The drying and removing of the solvent in step (2) is carried out under vacuum conditions; the heat treatment is carried out under nitrogen protection conditions, and the heat treatment time is 3 to 10 hours.

7. The method for preparing a high-frequency, low-power-consumption Sendust soft magnetic material according to claim 1, characterized in that: The binder in step (3) is an epoxy resin binder solution or a silicone resin binder solution; the amount of the binder added is 0.2-1% of the mass of the alloy powder treated with insulation coating based on its solid content.

8. The method for preparing a high-frequency, low-power-consumption Sendust soft magnetic material according to claim 1, characterized in that: The temperature of the pressing molding in step (3) is 60-100° C. and the pressure is 500-800 MPa; the time of the annealing treatment is 15-120 min.

9. A high-frequency, low-power-consumption sendust soft magnetic material, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. Application of the high-frequency, low-power-consumption iron-silicon-aluminum soft magnetic material described in claim 9 in the fields of AI computing chips, servers and communication equipment.

Citation Information

Patent Citations

  • Soft magnetic material, dust core and method of producing soft magnetic material

    CN1965379A

  • Soft magnetic powder compound, core and electric reactor

    CN104217834A

  • Method for preparing film coating solution from modified nano-silicon dioxide

    CN105924017A

  • Dust core coated with silica-based insulation, method for manufacturing same, and electromagnetic circuit component

    CN108701519A

  • Soft magnetic powder compound and preparation method thereof, and composite magnetic powder core material and preparation method thereof

    CN116453796A